Persecution is no blessing: Matthew 5:10–12 as a ‘practical theodicy’ - Klinker-De Klerck, Myriam G.P. (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2026)
About 30 years ago, Hanson argued on linguistic, literary-critical, and cultural grounds, that the term μακάριος in the macarisms should be translated as ‘how honourable!’ rather than ‘blessed’. His proposal has had little impact on translations or commentaries to date, despite the issue’s linguistic, cultural, and theological relevance. In this article, I examine the honour discourse in Matthew 5:10–12 and in Matthew 10:1–42, where the topic of persecution is addressed. This investigation serves a dual purpose: to strengthen Hanson’s argument from a rhetorical perspective and to illustrate the theological and social relevance of his proposal. The results also confirm F.P. Viljoen’s statement that the macarisms ‘function as a practical theodicy’. Contribution: This article contributes to the interpretation of the term μακάριος in Matthew 5:3–12 and its theological implications. This is relevant with regard to the impact of the Beatitudes in shame-based societies.